Risk factors for liver‐related and non‐liver‐related mortality following a sustained virological response after direct‐acting antiviral treatment for hepatitis C virus infection in a real‐world cohort. Issue 5 (9th January 2023) - Kozuka, Ritsuzo; Tamori, Akihiro; Enomoto, Masaru; Muto‐Yukawa, Yoshimi; Odagiri, Naoshi; Kotani, Kohei; Motoyama, Hiroyuki; Kawamura, Etsushi; Hagihara, Atsushi; Fujii, Hideki; Uchida‐Kobayashi, Sawako; Kawada, Norifumi
Abstract: A direct‐acting antiviral (DAA)‐induced sustained virological response (SVR) reduces the risk of mortality. However, the risk factors associated with liver‐related and non‐liver‐related mortality following a SVR after DAA treatment are unclear. We assessed the incidence and risk factors of liver‐related and non‐liver‐related mortality in 1180 patients who achieved a SVR after DAA treatment. During the follow‐up period after DAA treatment (median duration, 1099 [range: 84–2345] days), 53 (4.5%) patients died: 15 due to liver‐related mortality, 25 due to non‐liver‐related mortality and 13 due to unknown causes. The all‐cause, liver‐related and non‐liver‐related mortality rates were 14.9, 4.2 and 7.0/1000 person‐years, respectively. In a multivariate analysis, the development of hepatocellular carcinoma (HCC) after DAA treatment ( p  = .009; hazard ratio [HR], 31.484), an estimated glomerular filtration rate (eGFR) at baseline ≤61.68 ml/min/1.73 m 2 ( p  = .015; HR, 6.607), and an α‐fetoprotein level post‐treatment ≥7.6 ng/ml ( p  = .041; HR, 18.490) were significantly associated with liver‐related mortality. Furthermore, eGFR ≤67.94 ml/min/1.73 m 2 at baseline ( p  = .012; HR, 3.407) and albumin–bilirubin (ALBI) grade ≥ 2 at SVR ( p  = .024; HR, 3.449) were significantly associated with non‐liver‐related mortality. Early diagnosis and therapeutic interventions for HCC development after DAA treatment are important to reduce liver‐related mortality. The ALBI grade, which reflects the hepatic functional reserve, is a useful predictor of non‐liver‐related mortality after a SVR induced by DAA treatment. Furthermore, the renal dysfunction caused by metabolic syndrome may affect prognosis even after eliminating hepatitis C virus.